2004
DOI: 10.3402/ijch.v63i1.17649
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for hospitalization and infection in Canadian Inuit infants over the first year of life - a pilot study

Abstract: The results of this pilot study provide support for undertaking larger epidemiological studies in order to clarify the role of these risk factors, so that future preventive efforts can be informed and effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 5 publications
1
7
0
Order By: Relevance
“…In the absence of direct measures, it is plausible that there may be more barriers to beginning breastfeeding if an infant's primary caregiver is not their biological mother, even if the biological mother is in frequent and continued contact with the infant, which is not uncommon in Inuit traditional adoptions. Indeed, previous community based research in Inuit populations supports a lower prevalence of breastfeeding in adopted infants compared to other infants [6,29]. The present findings are consistent with the possibility that the child's primary caregiver may have a significant influence on whether breastfeeding was initiated.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…In the absence of direct measures, it is plausible that there may be more barriers to beginning breastfeeding if an infant's primary caregiver is not their biological mother, even if the biological mother is in frequent and continued contact with the infant, which is not uncommon in Inuit traditional adoptions. Indeed, previous community based research in Inuit populations supports a lower prevalence of breastfeeding in adopted infants compared to other infants [6,29]. The present findings are consistent with the possibility that the child's primary caregiver may have a significant influence on whether breastfeeding was initiated.…”
Section: Resultssupporting
confidence: 93%
“…Published reports indicate anywhere from 17 to 42 % of Inuit infants are adopted and most of these adoptions occur shortly after birth and may be within the same family and household [29][30][31]. Failing to include all caregiver reports would likely exclude a substantially large proportion of Inuit infants and not provide information on determinants of breastfeeding in the larger population.…”
Section: Resultsmentioning
confidence: 98%
“…Presence of smokers in the home was associated with a significantly increased risk of lower respiratory tract infection in Sisimiut, Greenland, 10 and in Alaska. 29 Jenkins and colleagues 33 reported that 94% of Inuit infants in Iqaluit were exposed to environmental tobacco smoke in the home, like the rate of 94% we observed, and much higher than the frequency of about 25% found in southern Canada. 34 Although some studies have found some evidence of a dose-response effect of environmental tobacco smoke, 35,36 no "safe" level has been identified.…”
Section: Researchmentioning
confidence: 44%
“…The prevalence of smoking in the homes of infants and young children in northern Canada is much higher than is reported for Canada as a whole, where 25% of children under 12 years of age were exposed to ETS at home (Health Canada, 2001). Jenkins et al. (2004) reported that 85% of Inuit infants in a birth cohort from Iqaluit, Nunavut were exposed to ETS at home.…”
Section: Discussionmentioning
confidence: 99%